2019
DOI: 10.1002/jbm.b.34372
|View full text |Cite
|
Sign up to set email alerts
|

Intact polyaniline coating as a conductive guidance is beneficial to repairing sciatic nerve injury

Abstract: Endowing the conduit with conductivity has been an effective way to stimulate nerve growth and functional recovery. Here, conducting polyaniline (PANi) was used to construct a conductive guidance by coating on the surface of microtubes inserted in a three‐dimensional zein nerve conduit to study the repairing efficacy on peripheral nerve injury. PANi nanoparticles with a size of 20–30 nm were synthesized and coated on the surface of microtubes through layer‐by‐layer deposition. Then, conduits including microtub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 55 publications
(111 reference statements)
0
13
0
Order By: Relevance
“…It has also been reported that the size of polyaniline particles formed by the degradation of PLLA/polyaniline/TSA fiber scaffolds in vivo ranged from 2.5 to 3.1 nm, while macrophages were able to devour foreign particles of 10 nm size (Yao et al, 2019). Moreover, the polyaniline nanoparticles could be swallowed by macrophages, and foreign particles were mainly dispersed in vesicles and mitochondria of macrophages (Wang et al, 2019). In contrast to our results, the polyaniline nanoparticles produced after HSPS degradation did not cause inflammation in the heart, liver, spleen, lung, and kidney organs, and our results showed that polyaniline particles did not move to the organs.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that the size of polyaniline particles formed by the degradation of PLLA/polyaniline/TSA fiber scaffolds in vivo ranged from 2.5 to 3.1 nm, while macrophages were able to devour foreign particles of 10 nm size (Yao et al, 2019). Moreover, the polyaniline nanoparticles could be swallowed by macrophages, and foreign particles were mainly dispersed in vesicles and mitochondria of macrophages (Wang et al, 2019). In contrast to our results, the polyaniline nanoparticles produced after HSPS degradation did not cause inflammation in the heart, liver, spleen, lung, and kidney organs, and our results showed that polyaniline particles did not move to the organs.…”
Section: Discussionmentioning
confidence: 93%
“…Research studies on using artificial conductive NGCs to guide nerve regeneration have been widely carried out. , One kind of conductive NGCs is often composed of conductive CNTs and biodegradable polymers . Due to the nondegradability of CNTs, it is quite necessary and important to track the in vivo locations of the implanted CNTs after the degradation of the NGC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 125 ] However, the PANI film was destroyed at 4 months of implantation producing PANI debris‐induced steric hindrance and eliciting an inflammatory response. [ 128 ] Due to the ill‐timed degradation of PANI‐NGC implantation, the second operation is inevitable for mitigating the immune responses.…”
Section: Conductive Materials Applied In the Ngcmentioning
confidence: 99%